Pondok Pesantren Bustanul Huffaz As-Sa'idiyah, Sampang, Madura - AM, Taufiqurrakhman (SUHUF, 2009)
This writing is a description of the profile of the Islamic Boarding School (pesantren)Ã‚ for memorizing the QurÃ¢â‚¬â„¢anÃ‚ (tahfizÃ‚ al-QurÃ¢â‚¬â„¢an), under the supervisory of K.H. Aunur Rafiq which is located at Jl. K.H. Hasyim AsyÃ¢â‚¬â„¢ari, Sampang, Maduara, East Java. This pesantren which was established in 1917 by K.H. Said Ismail is the earliest pesantren tahfiz in Nusantara. Some aspects being studied are the history of its pesantren, the achievements, the facilities, the students, the alumni, the activities of santri, the curriculums, the method of memorizing the QurÃ¢â‚¬â„¢an being used, the sanad, as well as the institution of this pesantren.